2012
DOI: 10.1155/2012/797218
|View full text |Cite
|
Sign up to set email alerts
|

Transmetatarsal Amputation: A Case Series and Review of the Literature

Abstract: Foot ulceration is a major cause of morbidity amongst patients with diabetes. In severe cases of ulceration, osteomyelitis and amputation can ensue. A distinct lack of agreement exists on the most appropriate level of amputation in cases of severe foot ulceration/infection to provide predictable healing rates. This paper provides an overview of the transmetatarsal amputation (TMA) as a limb salvage procedure and is written with the perspective and experiences of the Department of Podiatric Surgery at West Midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…However, in a multiple regression model that included all factors together, it was revealed that the main indicators that could predict the outcome of TMA were insulin dependence, laboratory values of albumin and CRP, and the LRINEC score. Published failure rates of TMA range from 14% to 78% [16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Multiple confounders might explain discordant healing rates in published data: First, heterogeneity in studied patient cohorts, including diabetic and nondiabetic patients, or cases of traumatic TMA.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a multiple regression model that included all factors together, it was revealed that the main indicators that could predict the outcome of TMA were insulin dependence, laboratory values of albumin and CRP, and the LRINEC score. Published failure rates of TMA range from 14% to 78% [16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Multiple confounders might explain discordant healing rates in published data: First, heterogeneity in studied patient cohorts, including diabetic and nondiabetic patients, or cases of traumatic TMA.…”
Section: Discussionmentioning
confidence: 99%
“…10 The literature suggests TMAs lead to greater patient satisfaction due to the patient's ability to more immediately return to activities that require ambulation. 2 In literature comparing above-the-knee amputations to BKAs, there was evidence suggesting that patients with BKA have more issues with their wound due to the impaired microvasculature at this more proximal amputation. 7 One may suspect a similar microvasculature impairment at the level of the foot would lead to wound problems such as delayed healing at the site of the TMA.…”
Section: Discussionmentioning
confidence: 99%
“…1 The TMA is not without its problems; notably, it is associated with an unpredictable healing time, and muscular imbalance due to unopposed action of the gastrocnemius, tibialis anterior, and tibialis posterior muscles compounded by the loss of the extensor hallucis longus and extensor digitorum longus. 2,3 Despite this, the TMA is still considered the best and final attempt to attain limb salvage for the patient knowing that there may be complications and failure to avoid BKAs. The traditional TMA requires a viable plantar flap to provide protection of remaining metatarsal bones and closure.…”
Section: Introductionmentioning
confidence: 99%
“…Adjunctive soft tissue procedures such as tendo-Achilles lengthening and split tibialis anterior tendon transfer for muscular imbalance are needed to correct for the equinovarus deformity. In addition, special footwear modifications are needed to reduce complication rates (13). …”
Section: Distal or Minor Amputations For The Diabetic Footmentioning
confidence: 99%